Revisiting the issue of initiating greetings (salām) to non-Muslims and answering their greetings: a comparative analysis of fatāwā issued in Malaysia - Abd Rahman, Mohamad Zulkifli; Mat Jubri @ Shamsuddin, Mustafa; El Mesawi, Mohamed El Tahir (Department of Fiqh and Usul al-Fiqh, AHAS KIRKHS, IIUM, 2024)
In Malaysia, there are two main fatwā bodies that discuss the problems faced by the Muslim community, namely the state’s fatwā committee which exists in every state and in Wilayah Persekutuan and the national fatwā council which discusses problems on a national level. The existence of these institutions with separate legislative authority has caused conflicts and differences in fatāwā issued in Malaysia. Among the issues that have different fatwā is the issue of initiating greeting (salām) to non-Muslims and answering their greeting. This issue is very significant especially in today’s world as a negative view may arise when a Muslim refuses to respond to a greeting conveyed by a non-Muslim. At the same time, Muslims sometimes are hesitant to offer and answer greetings from non-Muslims due to scholars’ opinions regarding this issue. This raises concerns that require this issue to be discussed intellectually by highlighting scholars’ opinions and arguments. Therefore, this paper explores the views of Muslim scholars regarding three related issues, namely the issue of offering greetings to a group of Muslims and non-Muslims, offering greetings to non-Muslims and answering greetings offered by non-Muslims and fatāwā issued regarding this matter. In elaborating on the fatāwā and scholars’ opinions related to these issues, analytical and comparative methods will be utilised. The objective of this writing is to evaluate the fatāwā issued in this matter as well as scholars’ opinions by analysing the basis of their disagreements and to choose the preferred opinions based on the evidence and the context of Malaysia. This study concludes that the researchers find that the fatāwā which permit initiating and answering greetings from non-Muslims are preferable based on the fact that the evidence from aḥādīth related to the prohibition are tied to their respective causes of the emergence (sabab al-wurūd) and it is more suitable with the pluralistic context of Malaysia.